2004
DOI: 10.1161/01.res.0000149531.02904.09
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Myofilament Function Contribute to Left Ventricular Dysfunction in Pigs Early After Myocardial Infarction

Abstract: Myocardial infarction (MI) initiates cardiac remodeling, depresses pump function, and predisposes to heart failure. This study was designed to identify early alterations in Ca2+ handling and myofilament proteins, which may contribute to contractile dysfunction and reduced beta-adrenergic responsiveness in postinfarct remodeled myocardium. Protein composition and contractile function of skinned cardiomyocytes were studied in remote, noninfarcted left ventricular (LV) subendocardium from pigs 3 weeks after MI ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
131
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(150 citation statements)
references
References 66 publications
18
131
1
Order By: Relevance
“…16,17 2D ejection fraction was calculated as (EDA − ESA)/EDA × 100%. Also, blood samples were taken from the aorta and collected in EDTA anticoagulation tubes, centrifuged, and plasma was stored at − 80°C until further analysis.…”
Section: Surgerymentioning
confidence: 99%
“…16,17 2D ejection fraction was calculated as (EDA − ESA)/EDA × 100%. Also, blood samples were taken from the aorta and collected in EDTA anticoagulation tubes, centrifuged, and plasma was stored at − 80°C until further analysis.…”
Section: Surgerymentioning
confidence: 99%
“…It has also been shown that CaMKII can act to mediate troponin I function [8] and the promoter-region of the atrial myosin light chain-1 gene [25]. It now appears that CaMKII may be able to acutely induce a shift in the myofilament sensitivity to Ca 2+ to a more energetically favorable state after exercise training, although other studies have suggested that PKA mediates Ca 2+ sensitivity [26]. This is conceivable also in the current study, since CaMKIIblockade only partially blunted the training-induced increase in Ca 2+ sensitivity.…”
Section: Myofilament Ca 2+ Sensitivitymentioning
confidence: 99%
“…Since most of the abundant cytoplasmic proteins, i.e., the cytosolic and myofilamental proteins, as well as the most abundant nuclear proteins, i.e., the histones, are removed, the resulting nuclear protein extract appears to be aptly suited for further analysis of TF abundance and function. We are planning to apply this method to nuclear proteome profiling on remodeled [26] and hibernating [24] myocardium. Since there is minimal contamination of the nuclear protein extract with cytosolic proteins, this method is highly useful for the analysis of nuclear presence of TFs in different conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac tissue was collected from a total of 18 Yorkshire × Landrace swine. Animals were sedated by an intramuscular injection of a mixture of ketamine and midazolam, anesthetized with intravenous pentobarbital (bolus + continuous infusion), intubated, and ventilated [24,26]. The thorax and pericardium were opened and the heart was exposed.…”
Section: Experimental Animalsmentioning
confidence: 99%
See 1 more Smart Citation